Duration of Hydraulic Flushing and its Effect on Sediment Bed Movement - Bong, Charles Hin Joo; Tze, Liang Lau; Aminuddin, Bin Ab Ghani (2017)
Hydraulic flushing is the most widely used method for sediment removal in sewer. However, open storm sewer tend to have longer flushing duration as compared to closed conduit sewer. This is due to storm water could enter more directly and rapidly into open storm sewer especially during rain events. The current study aims to determine the effect of flushing duration on the efficiency of sediment removal which is lacking in the literature. Flushing experiment was conducted in a rectangular flume for varying flushing durations namely approximately 3 seconds, 30 minutes and 60 minutes. Changes of the sediment bed profile were observed after each flush. Findings from the experiment has shown that short duration flushing is more efficient in terms of more sediment volume being removed as compared to long flushing duration. In terms of mean sediment bed front advancement, long flushing duration will moved the sediment bed front further than short duration flushing. The knowledge from the current study can be used to design a more efficient flushing devices for the management and active control of sediment in sewer system.